FIRST STAGES OF THE POST-FIRE NATURAL REGENERATION OF VEGETATION IN THE VENTANILLA WETLANDS (LIMA-PERU) - Aponte, Héctor (2017)
In the wetlands of Peru’s central coast, fires are a recurrent problem. Little is known concerning their impact on vegetation and the recovery strategies adopted by that vegetation in response to such events. The goal of this study is to provide information regarding changes in vegetation cover, density, growth and plant species diversity during the first 155 days after a fire that occurred at the Ventanilla Wetlands Regional Conservation Area (RCA). In order to evaluate the area, 51 plots, each measuring 1m2, were established. In these, the following information was recorded: a) Number of stems that survived the fire, divided by species; b) The length of new shoots, divided by species; c) The phenological stage of each stem; and d) Plant cover, obtained via visual estimation. Schoenoplectus americanus (bulrush) was the fastest to recover, followed by Distichlis spicata-Sporobolus virginicus (saltgrass). The only stems found to have survived the fire were those of S. americanus, and these began to die from day 45 onwards. Sarcocornia neei, Typha domingensis and Bolboeschoenus maritimus appeared after the event. Throughout the period of the study, the only species to flower was S. americanus, which began to flower from day 31. The Shannon Wiener and Simpson index values show that alpha diversity seems to have reached its highest value in the evaluated time and begins to decrease. Two important post-fire stages were identified for S. americanus (bulrush): a) The survival stage; and b) The growth stage. S. americanus has demonstrated a great ability to recover in the first stages following this ty of anthropogenic impact, achieving an average cover of 82% and representing 81% of the total abundance of stems during the first 155 days of evaluation.